Optimalisasi Pemanfaatan Lidi Sawit Sebagai Bahan Baku Kerajinan Tangan untuk Pemberdayaan Ekonomi Lokal - Yuliza, Mai; Usvita, Mega; Darlisma, Darlisma (Transpublika Publisher, 2025)
West Pasaman Regency has great potential in managing palm frond waste that has not been fully explored. This community service activity aims to achieve the following main objectives: (1) identify the problems and needs of the Maju Bersama Business Group, (2) provide solutions based on the identification of existing problems in the Maju Bersama Business Group, (3) increase community participation in the utilization of palm fronds, (4) increase community income through the utilization of palm fronds. The activity partner is the Maju Bersama Business Group led by Mrs. Sesdia Neri, located in Jorong Kampung Pisang, Nagari Ampek Koto, Kinali District, West Pasaman Regency. The Maju Bersama Business Group was established in January 2024. The program stages include socialization, training, technology implementation, mentoring and evaluation, as well as program sustainability. Evaluation results show that 30% of participants understood very well, while 50% understood, and 20% adequately understood the material presented. Thus, it can be concluded that this activity successfully achieved its educational objectives, as all participants demonstrated adequate understanding of the material provided.